Relationship of Ethical Sales Behaviour with Customer Loyalty, Trust and Commitment: A Study with Special Reference to Retail Store in Mysore City - M. Kethan; Mahabub Basha S (PT FORMOSA CENDEKIA GLOBAL, 2022)
The customer is a king in the market. The mobility of the customer takes place when they don’t get favourable services from any firms. The customer can change their preference and buying decision due to many reasons, it could be because of poor services, poor quality of products, insufficient information about the product which is being purchased from sales person etc. The sale is one of the important aspects in the marketing. The effective marketing can attract huge customers, but efficiency of sales person can retain customers for a longer period of time. Hence ethical sales behaviour of salesperson and retailer plays a significant role in increasing sales volume of a firm, simultaneously, increasing customer satisfaction, loyalty and commitment. This study made an attempt to reveal the significance relationship between ethical sales behaviour with customer trust, loyalty and commitment of bank employees towards concerned retail shop in Mysore City. The structured questionnaire was prepared and distributed among fifty respondents. Questionnaire will be given to the bank employees those who regular customer of a retail shop.